Entropy production minimization and non-Darcy resistance within wavy motion of Sutterby liquid subject to variable physical characteristics - Hayat, T.; Bibi, Farhat; Khan, A. A.; Alsaedi, A. (Journal of thermal analysis and calorimetry, 2021)
Non-Darcy resistance in peristaltic transport of Sutterby liquid in curved configuration is modeled. Variable characteristics of material (i.e., thermal conductivity and viscosity) are taken as temperature-dependent. Soret and Dufour features have also been retained. Problem is modeled by using conservation laws. Long wavelength and small Reynolds number have been invoked. Resulting problems have been solved numerically. Entropy optimization analysis is made. Axial velocity, temperature, concentration, entropy, Bejan number and heat transfer rate are examined for influential variables. It is found that velocity increases for variable viscosity coefficient and porous-space parameter. Temperature decreases for increased values of variable thermal conductivity. Opposite behavior of mass and energy is noted for Soret and Dufour parameters. Entropy minimized for thermal conductivity and viscosity coefficients. Entropy enhancement is noticed for Soret and Dufour parameters. Heat transfer rate at upper wall is enhanced for Soret and Dufour variables.